2002
DOI: 10.1038/sj.bjp.0704563
|View full text |Cite
|
Sign up to set email alerts
|

Probucol preserves endothelial function by reduction of the endogenous nitric oxide synthase inhibitor level

Abstract: 1 Oxide low-density lipoprotein (ox-LDL) is believed to play an important role in early events of atherogenesis, and asymmetric dimethylarginine (ADMA) is associated with the development of endothelial dysfunction. The present study examined the eect of a single injection of native lowdensity lipoprotein (LDL) on endothelium function and the serum level of ADMA and the eect of probucol on endothelium function and ADMA level in rats. 2Endothelial injury was induced by intravenous injection of LDL at the dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 31 publications
1
49
1
Order By: Relevance
“…Statins are known to correct endothelial dysfunction 30,85 and recently Simvastatin was shown to increase eNOS activity and ameliorate vasospasm 56 . Yet another cholesterol-lowering drug, probucol, was shown to promote functional reendothelization of stripped aorta 48 and to preserve endothelial vasodilatory functions by reducing ADMA levels 38 . Thus, we used probucol, a drug with high octanol/water partition coefficient (logP=10.91) 85 assuring significant penetration of the blood-brain barrier, to inhibit increased ADMA levels in CSF after SAH and prevent development of vasospasm in a primate model of SAH 73 .…”
Section: Another No Addressing Therapies For Cerebral Vasospasmmentioning
confidence: 99%
“…Statins are known to correct endothelial dysfunction 30,85 and recently Simvastatin was shown to increase eNOS activity and ameliorate vasospasm 56 . Yet another cholesterol-lowering drug, probucol, was shown to promote functional reendothelization of stripped aorta 48 and to preserve endothelial vasodilatory functions by reducing ADMA levels 38 . Thus, we used probucol, a drug with high octanol/water partition coefficient (logP=10.91) 85 assuring significant penetration of the blood-brain barrier, to inhibit increased ADMA levels in CSF after SAH and prevent development of vasospasm in a primate model of SAH 73 .…”
Section: Another No Addressing Therapies For Cerebral Vasospasmmentioning
confidence: 99%
“…There is evidence that an increase in ADMA is related to oxidative stress, and treatment with antioxidants, e.g. vitamin E, probucol, daviditin A and pyrrolidine dithiocarbamate, decreases both lipid peroxide and ADMA levels [26,27,28,29,30,31]. It was reported that Ang II can enhance the activity of NADPH oxidase and lead to marked ROS generation in cultured endothelial cells [32] and L6 myotubes, which is blocked by ARB losartan or the NADPH oxidase inhibitor apocynin [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the attenuation of DDAH activity by oxidative stress [8], whereby a cysteine molecule held in an activated state in the tertiary structure of the enzyme is inactivated by oxidation, may lead to an accumulation of ADMA. Antioxidants have been shown to decrease ADMA levels in cultured human endothelial cells [9] and in vivo rats exposed to native low-density lipoprotein [10]. Consequently, antioxidant therapy may reduce ADMA levels by attenuating the effects of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%